Can a Different Formulation of Vitamin D3 Allow Savings? An Analysis From an Italian Regional Perspective. (10th July 2019) - Sanò, Mario; Dutto, Patrizia; D'Anna, Stefano; Rognoni, Carla
Vitamin D3 reported in Italy in 2017 the net expenditure of almost €180 million, reaching the first place for consumption and the third place for conventional pharmaceutical spending. The aim of the study was to evaluate whether a shift of vitamin D3 prescriptions toward 100 000 IU formulation, less costly, could allow savings from the health-care perspective. An approach promoting the prescription of this formulation has been applied in a local health authority (ASL CN2) in Piedmont Region (Italy) starting from 2015. The retail pharmaceutical market and the consumption of vitamin D3 has been analyzed from year 2014 to 2017 in order to evaluate differences in expenditures. Despite an increase in consumption, the introduction of the new formulation enabled ASL CN2 to save about €280 000 in 2017 considering the regional average expenditure per 1000 inhabitants as a reference. If Piedmont Region had presented an average expenditure in line with that of ASL CN2, the annual regional savings would have exceeded €7 million in 2017 alone. A shift of vitamin D3 prescriptions toward 100 000 IU formulations would allow reducing costs from the payer perspective. Savings may be used to contain public pharmaceutical expenditure or can be allocated to fund other health-care technologies and services.